2017
DOI: 10.1371/journal.pone.0175904
|View full text |Cite
|
Sign up to set email alerts
|

Hair and stress: A pilot study of hair and cytokine balance alteration in healthy young women under major exam stress

Abstract: Mouse models show that experimental stress mimicking prolonged life-stress exposure enhances neurogenic inflammation, induces adaptive immunity cytokine-imbalance characterized by a shift to Type 1 T-helper cell cytokines and increases apoptosis of epithelial cells. This affects hair growth in otherwise healthy animals. In this study, we investigate whether a prolonged naturalistic life-stress exposure affects cytokine balance and hair parameters in healthy humans. 33 (18 exam, 15 comparison) female medical st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 97 publications
2
24
0
2
Order By: Relevance
“…In other studies chronic mental stress in the form of caregiving has been shown to be associated with increased CD62P reactivity (Aschbacher et al 2008). While this demonstrates that chronic mental stress due to an exam preparation certainly differs from that of caregiving or childhood trauma, it has nevertheless been shown previously to be associated with immunological and other biological changes (Marshall et al 1998;Peters et al 2017).…”
Section: Chronic Mental Stress Affects Platelet Cd63 Expressionmentioning
confidence: 83%
“…In other studies chronic mental stress in the form of caregiving has been shown to be associated with increased CD62P reactivity (Aschbacher et al 2008). While this demonstrates that chronic mental stress due to an exam preparation certainly differs from that of caregiving or childhood trauma, it has nevertheless been shown previously to be associated with immunological and other biological changes (Marshall et al 1998;Peters et al 2017).…”
Section: Chronic Mental Stress Affects Platelet Cd63 Expressionmentioning
confidence: 83%
“…It is when HF IP is lost that inflammatory hair diseases, such as alopecia areata and lichen planopilaris, develop (Bertolini et al, 2016;Harries et al, 2013;Imanishi et al, 2017;Strazzulla et al, 2018). Despite growing evidence that the HF's immune microenvironment may have an important regulatory role in regulating hair growth (Castellana et al, 2014;Kloepper et al, 2013;Maurer et al, 1995;Peters et al, 2017), in addition to their immune function, work so far has tended to focus on mouse HFs. Specifically in rodent skin, the HF mesenchyme (connective tissue sheath [CTS]), is densely populated with macrophages (MF) (Bertolini et al, 2013;Christoph et al, 2000;Paus et al, 1998), which fluctuates greatly during the hair cycle, being the highest during active hair growth (anagen), showing a sharp decline during regression (catagen) and reaching the lowest count in telogen (Paus et al, 1998).…”
Section: Ethics Statementsmentioning
confidence: 99%
“…However, greying in both mice and humans has been shown to be a relatively irreversible phenomenon driven in part by a depletion of melanocyte stem cells, although some stem cells and transient amplifying cells do remain ( Trueb and Tobin, 2010 ). In humans, recent evidence suggests hair growth and pigmentation changes in response to stress ( Peters et al, 2017 ), but this relationship, along with reversal of greying, remain insufficiently understood. The paucity of quantitative data in humans is mostly due to the lack of sensitive methods to precisely correlate stressful psychobiological processes with hair pigmentation and greying events at the single-follicle level.…”
Section: Introductionmentioning
confidence: 99%